ANALISIS YURIDIS TERHADAP PROSES LELANG JAMINAN GADAI DI PT.PEGADAIAN (PERSERO) UPC SUNGAI RAYA DALAM KOTA PONTIANAK - NIM. A1011211043, REVA DWI UTAMI (Jurnal Fatwa Hukum, 2025)
Abstract This study aims to analyze the auction process of pawned collateral at PT. Pegadaian (Persero) UPC Sungai Raya Dalam, Pontianak City, and to assess its compliance with the prevailing legal provisions, particularly in terms of transparency and public access to information. The background of the research is based on the importance of legal protection for customers and the need to evaluate auction procedures as a form of execution of rights over collateral assets. This research employs a normative and empirical juridical approach. The normative approach involves the examination of regulations related to the auction of pawned collateral, while the empirical approach is carried out through interviews with representatives of PT. Pegadaian (Persero) UPC Sungai Raya Dalam and members of the community. The study is descriptive-analytical in nature, using primary data obtained from interviews and secondary data from legal literature and relevant documents. Data collection techniques include literature study, interviews, and documentation, which are then analyzed qualitatively to assess the conformity of auction practices with legal norms and principles of transparency. The research findings indicate that, in general, the auction process of pledged collateral by PT. Pegadaian has complied with the applicable legal provisions, including the Civil Code (KUHPer), OJK Regulation Number 31/POJK.05/2016, Ministry of Finance Regulation Number 122/PMK.06/2023, and SOE Ministerial Regulation PER-2/MBU/03/2023. The stages of the auction process include the identification of pledged items, internal notification, valuation and appraisal, auction announcement, auction implementation, and recording of auction results. Although the procedures are generally in accordance with regulations, discrepancies were found in practice"”particularly in the announcement stage, which has not been carried out optimally and has not reached the wider public. This contradicts the principles of transparency and public access to information, which should be fundamental in the implementation of auctions by state-owned financial institutions. Therefore, this study emphasizes the importance of improving public outreach and information disclosure at every stage of the auction process, as well as the need for stricter oversight of auction practices by PT. Pegadaian. Keyword : Auction Procedures, Pawn Guarantee, PT. Pegadaian Abstrak Penelitian ini bertujuan untuk menganalisis proses pelelangan jaminan gadai di PT. Pegadaian (Persero) UPC Sungai Raya Dalam Kota Pontianak serta menilai kesesuaiannya dengan ketentuan hukum yang berlaku, terutama dari sisi transparansi dan keterbukaan informasi kepada masyarakat. Latar belakang penelitian didasari oleh pentingnya perlindungan hukum terhadap nasabah dan perlunya evaluasi terhadap prosedur lelang sebagai bentuk eksekusi hak atas barang jaminan. Penelitian ini menggunakan pendekatan yuridis normatif dan empiris. Pendekatan normatif dilakukan dengan menelaah peraturan terkait pelelangan barang jaminan gadai, sedangkan pendekatan empiris melalui wawancara dengan pihak PT. Pegadaian (Persero) UPC Sungai Raya Dalam dan masyarakat. Penelitian bersifat deskriptif-analitis, dengan data primer dari wawancara dan data sekunder dari literatur hukum dan dokumen relevan. Data dikumpulkan melalui studi pustaka, wawancara, dan dokumentasi, lalu dianalisis secara kualitatif untuk menilai kesesuaian praktik pelelangan dengan hukum dan prinsip transparansi. Hasil penelitian menunjukkan bahwa secara umum, proses pelelangan barang jaminan telah mengikuti ketentuan KUHPer, POJK Nomor 31/POJK.05/2016, PMK No.122/PMK.06/2023, dan PER-2/MBU/03/2023. Proses pelelangan dimulai dari penentuan barang lelang, pemberitahuan lelang, penilaian dan penaksiran barang, pengumuman lelang, pelaksanaan lelang, dan hasil lelang. Namun, ditemukan beberapa ketidaksesuaian dalam p-raktiknya, terutama dalam aspek pengumuman lelang yang belum optimal disampaikan kepada masyarakat luas seperti yang terdapat di PMK No.122/PMK.06/2023. Hal ini menimbulkan persoalan mengenai akses informasi dan minimnya transparansi, yang semestinya menjadi prinsip utama dalam pelaksanaan lelang oleh lembaga keuangan negara. Dengan demikian, penelitian ini menekankan pentingnya peningkatan sosialisasi dan keterbukaan informasi publik dalam setiap tahapan lelang, serta perlunya pengawasan yang lebih ketat terhadap pelaksanaan lelang oleh PT. Pegadaian. Kata Kunci : Prosedur Lelang, Jaminan Gadai, PT. Pegadaian.